Extension interventions in coping of farmers against effect of climate change in dairy farming - Ponnusamy, Kuppusamy; Chakravarty, Ritu; Singh, Sohanvir (Indian Journal of Dairy Science, 2019)
Climate change is becoming a major concern for farmers due to its effect on productivity and consequently profitability. ICAR started NICRA project in 2011 and still continue strategic and applied research endeavors. NDRI Implemented Technology Demonstration Component of NICRA in three adopted villages viz. Manglora, Dilawara and Sohana in Karnal district during 2011-2017. Heat stress and fodder scarcity were identified as major climate sensitive issues affecting the productivity of dairy farming. Village Climate Risk Management Committee (VCRMC) was constituted in three villages for planning and implementing technological interventions to combat the effects of climate change. Area specific mineral mixture (50 g/day/animal), vitamin E supplementation (1000 IU/animal/day), mustard oil (50 ml/day/animal) and supplementation of sodium and potassium salt (30 g/week) had resulted in sustaining the milk productivity and in certain cases helped farmers to increase 0.5 litre milk productivity/day/animal. Manure pit, seasonal dairy products, periodic deworming, NICRA calendar, awareness camps and regular training had also contributed to create more awareness and facilitated the adoption of prescribed technological interventions and farmers were convinced of the utility of interventions.